Analysis of Health Expenditure on Rice Expenditure: A Case Study of Vulnerable Poor Households on Sulawesi Island - Santi Yunus; Chairil Anwar; Mohamad Ichwan; Rita Yunus (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Poverty reduction under the Sustainable Development Goals remains constrained by the persistence of vulnerable poor households, particularly in Sulawesi, where limited income and rising health expenditures increase the risk of falling into poverty despite being above the poverty line. This study aims to determine the income of vulnerable low-income households on Sulawesi Island using SUSENAS 2023 data and to analyze the ratio of health expenditure to rice expenditure. It is descriptive quantitative research using SUSENAS 2023 secondary data. The research population is 47,478 households, focusing on a sample of 9,223 vulnerable low-income households defined by expenditure of 1.0-1.5 times the provincial poverty line. Results show 9,223 vulnerable low-income households spread across six provinces. Central Sulawesi has the highest vulnerability threshold, while West Sulawesi has the lowest, reflecting regional price differences. Living costs increase economic vulnerability. The proportion of non-prescription health expenditure is highest in Central and Southeast Sulawesi, where it exceeds rice expenditure. Purchasing non-prescription drugs is common due to easier access and lower cost, despite risks of irrational use. Government social assistance for low-income households includes direct cash transfers, national health insurance, and food aid.